Exploring the role of municipal public accounts committee in enhancing accountable service delivery : the case of Makhado Local Municipality in Limpopo Province, South Africa - Malange, Tshinanne Maria (My University, 2025)
The municipal public accounts committees (MPACs) within the South African local municipalities requires much capacity building to enhance their role to hold public officials accountable for the public accounts as well as enhance accountable service delivery. In this regard, political oversight was identified as an effective resource to enhance service delivery. The study sought to establish the significance of political oversight in public accounts; reasons why South African communities protest service delivery; why the protests have become so violent; as well as factors and reasons attribute towards the poor delivery of services. The study also explored effective ways to alleviate corruption amongst public officials, the composition of the MPACs, and capacity building of latter committee members. The pragmatist paradigm underpinned the research. A qualitative research approach and a multiple case study research design was adopted to inform the study about the significance of the application of the data collection methods, for example, interviews and questionnaires. Twelve research respondents participated in the interviews, while 150 completed the questionnaire. The purposive sampling procedure was utilised to select the research participants. The methods to gather data included interviews and questionnaires which represented the mixed method, qualitative and quantitative approaches respectively. The data analysis process was conducted through two primary procedures, namely, thematic and quantitative data analysis. These strategies represented the qualitative and the quantitative research approaches, respectively. The regulatory framework for this study was formulated on the need to utilise public funds in a responsible way. In this regard, the regulatory framework for the study was informed by a series of legislative frameworks including the Constitution of the Republic of South Africa, 1996 (Act 108 of 1996); Public Finance Management Act, 1996 (Act 1 of 1996); Municipal Public Finance Management Act, 2003 (Act 56 of 2003); Municipal Structures Act, 2000 (Act 117 of 2000); and Public Service Act, 1994 (Act 103 of 1994). The reviewed literature supported the ideas that political oversight should be viewed as an important resource to manage public accounts at local municipal level; public officials should be held accountable for the public funds, which is the root causes attributed for the poor delivery of services; effective measures be implemented to identify significant alleviation of corruption amongst public officials; and the composition of the MPACs as well as the effective capacity building for its members. The research findings supported the enhancement of MPACs’ oversight role to enhance processes related to capacitating members in workshops, training and exposure to further education and training at colleges and universities in South Africa. Furthermore, many the research respondents revealed that law enforcement processes should be enhanced to criminalise public officials who were found guilty of mismanaging public funds. A series of recommendations included that the national government’s SCOPA was identified as the most effective approach to enhance the role of the MPACs’ management and operations, for example, the latter committee should benchmark good management, administration and operations to achieve oversight of the politicians responsible for public accounts. It was also recommended that local municipalities ensure that they hold respective public officials accountable; public participation should be considered as one of the most important approaches to improve MPACs’ accountability to provide effective and efficient service delivery; higher education and training institutions, namely, colleges and universities should be involved in the provision of knowledge and skills related to the oversight role to enhance accountable service delivery; and further studies be conducted to re-engineer the role of municipal public accounts committees. The latter was to ensure accountable service delivery; harsher measures to deal with corrupt public officials who loot the public funds; and the need to include research and innovation to improve the management and operations of the municipal public account’s committees within the South African context.
Thesis (MPAM.) -- University of Limpopo, 2025
Keywords: Political oversight; Municipal public accounts committee; Service delivery; Capacity building; Municipal services -- South Africa; Municipal services -- Finance; Corruption; Municipal government -- South Africa -- Limpopo; Generational accounting